Salivary Cortisol as a Biomarker to Explore the Role of Maternal Stress in Early Childhood Caries - Sharat Chandra Pani; Deena Abuthuraya; Hadia M. AlShammery; Dalal AlShammery; Hind AlShehri (International Journal of Dentistry)
Objective. To compare salivary cortisol levels of children with ECC and their mothers with those of caries free children from a similar sociodemographic cohort. Design. Sixty-four college-educated, working mothers from middle income families with no history of anxiety disorders and their first born children aged between 48 and 71 months were included in the study. Salivary cortisol levels were analyzed using electrochemiluminescence (ECL) immunoassay. Statistical Analyses. Significance of difference between the cortisol levels of children with ECC and control children and of their mothers was analyzed using the Student’s t- test. The intraclass correlation coefficient was used to measure the significance of correlation of cortisol levels between the mother and the child with logistic regression to explore possible associations. Results. Mothers of children with ECC had significantly higher levels of salivary cortisol () than mothers of caries free children. The salivary cortisol levels of children with ECC were significantly higher than caries free children (). A significant correlation existed between the salivary cortisol level of the mother and that of the child (). Conclusion. While salivary cortisol levels of the child seem to have a direct impact on the incidence of ECC, maternal stress seems to have an indirect effect.